Approximation of classes of convolutions by linear methods of summation of Fourier series - Bushev, D. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider a family of special linear methods of summation of Fourier series and establish exact equalities for the approximation of classes of convolutions with even and odd kernels by polynomials generated by these methods.